Follow up coronary vessel evaluation of magnesium bioresorbable stents with coronary computed tomography angiography. (14th October 2021) - Pozo Osinalde, E; Salinas, P; Cerrato, E; Garcia Blas, S; Varbella, F; Parrilla Munoz, C; Vaudano, G P; Bustos, A; De Agustin, J A; Macaya, C; Escaned, J
Abstract: Background: Cardiac computed tomography angiography (CCTA) has already shown its ability to evaluate late results of polymer-based bioresorbable scaffolds (BVS) in different clinical scenarios. Recently, magnesium-based BVS (Mg-BVS) has emerged as an interesting alternative to these previous platforms due to its lower risk of thrombosis. Nonetheless, there is no systematic data about characterization of magnesium BVS with CCTA. Purpose: To study the feasibility of Mg-BVS assessment with CCTA and to evaluate in-scaffold wall tissue characterization during the follow-up. Methods: In this multicentre work, CCTA was performed in patients with a previously implanted Mg-BVS as a supplementary follow-up assessment. All studies were done after the theoretical resorption time of the scaffolds. A central core laboratory with an independent level 3 expert in CCTA blinded to the clinical and angiographic results analysed the studies. For this purpose, a dedicated software for coronary analysis was used to quantify coronary stenosis and evaluate coronary wall (Figure). Results: Eight patients (55±6 years-old; 87.5% male) with a previously implanted Mg-BVS from 3 different centres in Spain and Italy were included. The presentation was equally distributed (2, 25%) among stable and unstable angina, NSTEMI and STEMI. Target vessels included 5 left anterior descending (62.5%), 2 left circumflex (25%) and 1 right coronary arteries (12.5%). CTCA was performed 13 [11.3–20] months after BVS implantation. In spite of the blinding, all scaffolds were accurately located through identification of proximal and distal radiopaque markers. Concordance of CCTA Mg-BVS sizing was good for diameter (ICC 0.66; p=0.09) and excellent for length (ICC 0.98; p<0, 001) of the stents. Patency of all scaffolds was confirmed without significant diameter (0.14 [0–0.27]%) or area (0.39 [0.19–0.57]%) stenoses compared with proximal reference segments. Moreover, within the stent boundaries the maximum luminal diameter and area narrowing were 0.22 [0, 12–0.3]% and 0.39 [0.23–0.5]% respectively, in keeping with mild in-scaffold late loss and/or underlying plaque growth. Regarding coronary wall tissue characterization of segments with BVS, there was a plaque burden of 0.37 [0.31–0.48]% and plaque volume of 87.6 [50.2–189.3] mm 3 . The most common component of the plaque was fibrous (69.5 [33.9–133.7]%), suggesting that Mg-BVS allows for stabilization of unstable culprit lesions (6/8 cases). Compared to the proximal and distal reference segments, there was no differences in plaque volume or composition, suggesting a good coronary vessel healing. Conclusions: This short series shows for the first time the ability of CCTA to correctly locate and evaluate patency of Mg-BVS. Moreover, the lack of metal struts allows a detailed coronary plaque evaluation at treated segments. These preliminary results suggest plaque stabilization and a good coronary vessel healing with this novel scaffold. Funding Acknowledgement: Type of funding sources: None.